Effect of Surface Treatment on the Mechanical Performance of Unidirectional Enset Fiber Reinforced Polypropylene Composite. Issue 14 (28th October 2022) - Dessie, Esubalew; Yiping, Qiu; Tesfaye, Tamrat; Gideon, Rotich Kipchirchir; Fanxizi, Liu
ABSTRACT: Natural fibers have recently become an alternative reinforcement for composite products owing to their light-weightiness, renewability and biodegradability. However, they have certain drawbacks including hygroscopic nature, low compatibility with the polymer matrices and inferior mechanical properties when compared to synthetic fibers. This study aims to develop a one-way enset fiber-reinforced polypropylene (PP) composite. In this study, long and aligned enset fibers were interlaced with PP yarns to form a woven mat. The mat was surface treated, and later the film stacking method was applied to develop the composite via hot pressing. The mechanical properties of the developed composites were characterized. The results showed that bis[3-(triethoxysilyl) propyl] tetrasulfide (1.5 wt% Si69) and 3glycidyloxy propyl trimethoxy silane (5 wt%GPs) treated unidirectional enset fiber woven mat showed the highest tensile strength which shows an increase of 266.98% and 218.14%, respectively, relative to the pure PP. In terms of flexural strength, enset fibers treated with NaOH (3.5 wt%) and EVsi69 (1.5 wt%) showed the greatest improvement of 218.14% and 151.64% respectively over pure PP. Therefore, the developed composite samples confirmed that enset fiber can be effectively reinforced with PP for the application of automotive and construction industries.